Linguistic and nonlinguistic processing speed across age-matched normal healthy controls and individuals with left-hemisphere damage, with and without aphasia. Issue 2 (1st February 2022) - Yoo, Hyunsoo; McNeil, Malcolm R.; Dickey, Michael Walsh; Terhorst, Lauren
ABSTRACT: Background: Slowed language production and comprehension in people with aphasia (PWA) is frequently cited as a characteristic of the disorder, even after full recovery. However, results supporting the existence of slowness are inconsistent and the mechanisms are unclear. Previous research has failed to determine the neurocognitive locus of the slowing and whether it is due to left hemisphere damage, general aging, or language-specific mechanisms. The goals of this study are: (1) to explore whether reduced processing speed is present and specific to the presence of aphasia or due to left-hemisphere damage more generally and (2) whether it is specific to the linguistic domain of cognition. Results: The results of the mixed effects model revealed significant main effects for groups and domains, and no significant interactions among groups or between domains. The two brain-damaged groups exhibited significantly longer processing times across tasks compared to the NHC group. The processing speed of the PWA group was significantly longer than that of the LHD group across simple perceptual and more cognitively complex tasks. Groups were not significantly different on three nonlinguistic sensory-motor tasks. Conclusions: Left-hemisphere damage-related slowing, as well as aphasia-additive slowing, was demonstrated as evidenced by significant differences between the two brain-damaged groups and between these two groups and the NHC group. Therefore, the observed slowing in the PWA group appears to be due to both brain-damage-related and aphasia-additive slowing. Domain-specificity was not observed as evidenced by significant slowing on both linguistic and nonlinguistic tasks in both brain-damaged groups compared to the performance of the NHCs.